The Implementation Of Social Interaction Based Morning Circle To Foster Early Childhood Self Confidence - Fathimah Nur Yasmin; Ahmad Khoiri; Vava Imam Agus Faisal (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Self-confidence is an essential aspect of early childhood social-emotional development; however, many children still demonstrate passive behavior and hesitation in expressing themselves during classroom activities. This study aimed to describe the implementation of a social interaction-based morning circle, identify the challenges encountered, and analyze its impact on children’s self-confidence development. The research employed a qualitative descriptive approach and was conducted at RA Masyithoh 02 Sirau, Banyumas. Data were collected through observation, semi-structured interviews, and documentation involving the principal, classroom teacher, and Group B children. The findings showed that the morning circle was implemented as a daily classroom routine consisting of greeting and welcoming activities, prayer and warm-up sessions, interactive core activities, theme introduction, and positive reinforcement. The implementation was conducted in a structured and consistent manner. Several challenges were identified, including differences in children’s characteristics, unequal participation levels, and children’s mood in the morning. Teachers addressed these challenges through engaging activities, guiding questions, simple games, and reinforcement strategies. The results indicated that the morning circle contributed positively to children’s self-confidence, reflected in their increased willingness to speak, answer questions, participate in group discussions, and interact with peers. The improvement occurred gradually through continuous practice and social interaction in a supportive classroom environment. Therefore, a social interaction-based morning circle can be considered an effective and practical strategy for fostering self-confidence in early childhood education settings and contributes to strengthening social-emotional learning practices in the classroom.